SIMULATION OF PATIENTS – LIFE SUPPORT COURSES ADVANCED TRAUMA LIFE SUPPORT - Scarpelini, Sandro; Andrade, José Ivan (Medicina (Ribeirao Preto), 2007)
During the last 30 years, the Advanced Trauma Life Support course from the American College of Surgeons became the worldwide reference in the trauma initial care education. Since the first course in Nebraska, 1978, it has been reproduced in more than 25 countries, due to its objective approach, dynamic and skilled based teaching of the life threatening situations of the trauma patient and the systematic training of the main surgical skills, fundamental to the success of the care. This course, based in artificial simulators, animal models, and actors seems to be a very efficient tool to the emergency medical education.